2009
DOI: 10.1007/s10096-009-0726-4
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of and prenatal molecular distinction between invasive and colonizing group B streptococci in The Netherlands and Taiwan

Abstract: The identification of markers for virulent group B streptococci (GBS) could guide prenatal prevention and intervention strategies. We compared the distribution of serotypes and potential pathogenicity islands (PPIs) between invasive and colonizing GBS. Colonizing and invasive strains from The Netherlands and Taiwan were serotyped. We used polymerase chain reaction (PCR) for the amplification of several new PPI markers. Several combinations of PPI-specific markers and serotypes were associated with invasiveness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…These findings corroborate the finding of other studies from industrialized country settings [31], [34], [36], [37]. Our study, however, clarified that the difference in serotype distribution between invasive and colonizing isolates is related to an increased invasive potential of certain GBS serotypes (i.e.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These findings corroborate the finding of other studies from industrialized country settings [31], [34], [36], [37]. Our study, however, clarified that the difference in serotype distribution between invasive and colonizing isolates is related to an increased invasive potential of certain GBS serotypes (i.e.…”
Section: Discussionsupporting
confidence: 92%
“…However, the invasive potential of serotype Ia is variable across different sites. In South Africa, Taiwan and The Netherlands [37], serotype Ia was less invasive than type III, although more invasive in Portugal [34], Israel [36] and Sweden [31]. The reasons for variation in invasive potential of serotype Ia reported at different sites are unclear, however data from Portugal suggests that the high invasive index of this serotype can be attributed to a dominant clone (ST-23 and ST-24), suggesting that the underlying genotype can influence the invasive potential.…”
Section: Discussionmentioning
confidence: 99%
“…All isolates were previously identified as GBS using both biochemical and molecular methods [14]. Strains were stored at −80°C.…”
Section: Methodsmentioning
confidence: 99%
“…A subset of 33 colonizing and invasive GBS isolates representing all seven of the important subtypes was obtained from a reference collection (Table 1 ) [ 14 ]. All isolates were previously identified as GBS using both biochemical and molecular methods [ 14 ]. Strains were stored at −80°C.…”
Section: Methodsmentioning
confidence: 99%
“…These virulence factors are coded in bacterial virulence genes, and these genes vary among GBS subtypes. Epidemiological research has consistently shown that specific GBS bacterial genotypes, such as CC17, are over-represented in invasive disease compared with colonization, strongly suggesting that invasive GBS strains have unique bacterial virulence genes [ 20 , 35 , 36 , 37 , 38 , 39 , 40 ]. The specificity of IAP strategies could possibly be improved not only by screening for GBS carriage, but also by incorporating multiple genetic markers into a single PCR test, making it possible to determine both the presence and the invasive potential of GBS bacteria [ 37 ].…”
Section: Maternal Perspectivementioning
confidence: 99%